PERAN ORANG TUA DALAM MENINGKATKAN KUALITAS PENYAMPAIAN MATERI GURU MELALUI MEDIA BELAJAR VIA DARING - Yasa, I Made Ardika; Kartika, Yuyun Dewi; Cahyani, Gusti Ayu Sintya Widi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Research related to the role of parents in increasing the effectiveness of delivering teacher material through offline learning media was carried out with the objectives of 1. To understand the role of parents during Covid-19, 2. To know the media and learning resources during Covid-19, 3. To analyze the role of people know in delivering teacher material during Covid-19. The Covid-19 pandemic has forced the government to carry out several emergency policies, one of which is Learning From Home (BDR). In this BDR activity, parents become a bridge of knowledge from teacher to child, so parents play an important role in online learning. Parents and teachers are expected to have good communication so that teaching and learning activities for children are not disturbed and can run. The government is expected to pay attention to the obstacles experienced by students, teachers, and parents.